SYNTHESIS OF POLY ORTHO BROMO ANILINE AND STUDY ITS APPLICATION - Shabeeb , Ghufran Mohammad; Haider Abdulelah (International Journal Multidisciplinary (IJMI), 2024)
After producing poly orthobromo aniline, FT-IR spectroscopy was used to investigate its structure. We examined the optical and electrical characteristics of poly-o-bromo aniline (o-BrAn) in this work. O-bromoaniline/Ag, an original polymer, has been combined. Several techniques, including FT-IR spectroscopy and UV-visible spectra, have been employed for analyzing the mixer. The nonlinear changes in voltage and current are demonstrated by the I-V characteristics.The conductivity values ranged from o-BrAnp is 5.6×10-8 S/cm , but at o-BrAn/Ag0.25 is 3.1×10-7 S/cm. Since the conductivity value of the material is in the range of semiconductor, it can be used in the field of organic semiconductors.